IMPLEMENTASI PERANGKAT PELATIHAN HIGIENE SANITASI UNTUK MENINGKATKAN KEMAMPUAN PENJAMAH MAKANAN â€œPIA IBU SLAMETâ€ DI TUGU KEPATIHAN KOTA JOMBANG - Mustaqimah, Thoriqotul (Jurnal Tata Boga, 2018)
Abstract This research was aimed to find out: 1) implementation of sanitation training for food handler hygiene, 2) activity of sanitation training of food handler hygiene, 3) result of sanitation test of food handler sanitation hygiene, 4) response of sanitation trainee of sanitation of food handler. This research is a pre-experiment research with pretest and post-test group design. The data obtained are the result of training implementation, the activity of the trainee, the pre-test and post-test result of improvement of food handler "Pia Ibu Slamet" hygiene sanitation, and the training participants response. Subjects were 33 trainees (food handlers). Technique of collecting data using test observation method and questionnaire. Data analysis technique using t test. The result of data analysis showed that the training of hygiene sanitation practitioners of food handlers obtained very good criteria with the percentage of 84.98%. The activities of trainees obtained an assessment with an average of 3.77 with very good criteria. Data of sanitation hygiene training of food handlers obtained from the pre-test and post-test values ??showed very significant differences with the pre-test value of 56.06 and the post-test 86.21 so that there was improvement of the ability of food handlers after the training on hygiene sanitation food handlers. Participants responses to training on hygiene sanitation of food handlers show an average percentage of 100% with very good criteria. Based on the research result, it can be concluded that sanitation hygiene training to food handler "Pia Ibu Slamet" in Jombang is able to improve the knowledge and skill of the trainee. Keywords: Training, sanitation hygiene food handlers.